The Development of Sasirangan Entrepreneurs In Banjarmasin: Study on Sharia-Based Business Perspective - S. Purnamasari; Purnama Rozak; Kurniaty; Ibrahim Dahiru Idriss (International Journal of Islamic Business and Economics (IJIBEC), 2023)
The aim of the study was to describe the knowledge of Sasirangan cloth entrepreneurs in Sasirangan Village and their perceptions of sharia-based venture capital loans. This type of research is field research which is a case study with a descriptive approach. The results of this study concluded that the knowledge of Sasirangan cloth entrepreneurs in Sasirangan Village regarding sharia-based business capital loans was still divided into3, namely: (1) knowing enough about providing sharia-based business capital loans, (2) not knowing about providing capital loans. sharia-based businesses, and (3) very little knowledge about providing sharia-based business capital loans. The perceptions of sasirangan cloth entrepreneurs in Sasirangan Village regarding sharia-based business capital loans also varied, namely: informants who had a good view of providing sharia-based business capital loans because they were banking based on sharia principles in their management and informants who thought that according to them, sharia banking and conventional are the same. The implication is knowing the knowledge and perceptions of Sasirangan Cloth MSME entrepreneurs in Sasirangan Village, Banjarmasin regardingsharia-based capital loans will be able to increase the economic growth of UMKM in Banjarmasin City, including having implications for the large number of workers absorbed so that they can become a driving force for theeconomy because they can also solvecurrent economic problems. This has hit the Indonesian nation, among others: creating jobs, increasing people's income, and alleviating poverty. Therefore, the researcher's suggestion is the need to increase Islamic financial literacy and inclusion for Sasirangan Fabric MSME actors in Sasirangan Village, Banjarmasin City by collaborating with related parties and in a sustainable manne.